2005
DOI: 10.1074/jbc.m500462200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Anti-platelet Monoclonal Antibody (3C7) Specific for the Complexof Integrin αIIbβ3 Inhibits PlateletAggregation and Adhesion

Abstract: Activation or ligand binding induces conformational changes in ␣ IIb ␤ 3 , resulting in exposure of neoepitopes named ligand-induced binding sites. We reported here a novel monoclonal antibody developed by using Chinese hamster ovary (CHO) cells expressing an activated ␣ IIb ␤ 3 mutant (CHO ␣ IIb ␤ 3 ⌬717) as the immunogen. This IgG 2b named 3C7 was specific for the complex of ␣ IIb ␤ 3 as demonstrated by flow cytometry, immunoprecipitation, and EDTA chelating. The binding of 3C7 to platelets increased signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Although antiplatelet monoclonal antibodies (mAbs) that are of great interest for analyzing platelet surface molecule functions have already been reported, 2,3 these mAbs were derived after xenogenic immunization and are therefore not fully reflective of antiplatelet autoantibodies. Mouse monoclonal antiplatelet autoantibodies have also been derived from (NZBxBXSB)F1 animals.…”
Section: Introductionmentioning
confidence: 99%
“…Although antiplatelet monoclonal antibodies (mAbs) that are of great interest for analyzing platelet surface molecule functions have already been reported, 2,3 these mAbs were derived after xenogenic immunization and are therefore not fully reflective of antiplatelet autoantibodies. Mouse monoclonal antiplatelet autoantibodies have also been derived from (NZBxBXSB)F1 animals.…”
Section: Introductionmentioning
confidence: 99%
“…Aggregation processes are initiated by the activation of αIIbβ3, which binds to fibrinogen and adjacent platelets (30,31). Chen et al (32) previously reported that anti-αIIbβ3 complex antibodies inhibited the aggregation of platelets. The present study examined the levels of αIIbβ3 to identify the effects of the LRRFIP1 on platelet agglutination.…”
Section: Discussionmentioning
confidence: 99%
“…The monoclonal antibody 3C7, which is directed against the complex aIIbb3, is also known to inhibit platelet aggregation. 16 However, this antibody was observed to bind to both non-activated and activated platelets, and as such would not be of use simultaneously in the diagnosis of the activation status of platelets in patients.…”
Section: Discussionmentioning
confidence: 99%